2019
DOI: 10.1111/nph.15645
|View full text |Cite
|
Sign up to set email alerts
|

Pollen tube integrity regulation in flowering plants: insights from molecular assemblies on the pollen tube surface

Abstract: Contents Summary687I.Introduction687II.Pollen tube membrane‐localized receptors coordinate cell integrity and sperm release689III.RALF peptides mediate autocrine and paracrine signaling689IV.ROS and ion channel signaling mediate intracellular response690V.Involvements from pollen tube cell wall components690VI.Concluding remarks691Acknowledgements692Author contributions692References692 Summary Unlike in animals, sperm in flowering plants are immotile and they are embraced as passive cargoes by a pollen tube … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 53 publications
0
54
0
Order By: Relevance
“…At anthesis, the pollen germination and pollen tube elongation are inhibited by heat stress, which was mainly inferred due to an energy imbalance (Zhang et al, ). Indeed, the pollen tube elongation into the ovary is an extremely energy‐consuming process, which appears to rely on plastid‐localized glycolysis and mitochondrial‐localized respiration pathways (Ge, Cheung, & Qu, ; Goetz et al, ). During this process, the respiration rates in the pollen tubes sharply increase, reaching up to 10 times higher levels compared with those of vegetative tissues.…”
Section: Introductionmentioning
confidence: 99%
“…At anthesis, the pollen germination and pollen tube elongation are inhibited by heat stress, which was mainly inferred due to an energy imbalance (Zhang et al, ). Indeed, the pollen tube elongation into the ovary is an extremely energy‐consuming process, which appears to rely on plastid‐localized glycolysis and mitochondrial‐localized respiration pathways (Ge, Cheung, & Qu, ; Goetz et al, ). During this process, the respiration rates in the pollen tubes sharply increase, reaching up to 10 times higher levels compared with those of vegetative tissues.…”
Section: Introductionmentioning
confidence: 99%
“…The small (~5 kDa), secreted, basic peptides RALF1 and RALF8 are members of the rapid alkalinization factor (RALF) family of plant peptides that affect plant growth, pathogen response, and pollen tube generation. [1][2][3][4][5] The importance of the family of RALF peptides in plants is supported by the presence of a large number of genomic DNA sequences encoding RALF and RALF-like peptides. A recent study of computationally identified RALF-like sequences describes 795 RALF coding sequences in 51 different plant species.…”
Section: Introductionmentioning
confidence: 99%
“…In the stage of pollen tube-stigma interaction in Brassicaceae, recognition of self S-locus cysteine-rich protein SCR in pollen by the stigma S-receptor kinase SRK leads to self-incompatibility [8]. After arriving at ovules, another group of cysteine-rich proteins, rapid alkalinization factors (RALFs) interact their corresponding receptors of the Catharanthus roseus RLK1-LIKE (CrRLK1L) family to play a critical role in controlling pollen tube reception [9,10]. Of particular interests, in the stage of pollen tube guidance in Arabidopsis, a group of synergid cell-specific cysteine-rich peptides AtLURE1s are attractive cues from female gametophyte to guide pollen tubes [11].…”
Section: Research Highlightmentioning
confidence: 99%